The Chaplain's call: crisis, care, and the ministry of presence: responding with hope in trauma, suicide, violence and abuse - Godwin-N, Gloria (Gloria Godwin-N, 2025)
"This essential chaplaincy manual is a powerful resource for those called to serve the hurting, the broken and the forgotten. Designed for both new and experienced chaplains, this guide offers biblical foundations and practical training for responding to real-world issues such as trauma, violence and sexual abuse, suicide and generational curses. Dr. Gloria Godwin-N, a certified chaplain and global spiritual leader, combines her years of ministerial experience with compassionate insight. Each chapter walks readers through complex situations chaplains often face in schools, hospitals, prisons, senior care centers, disaster zones, and communities. Rooted in scripture, this book equips readers with spiritual discernment , emotional intelligence and ethical care practices. You will find guidance on crisis intervention, comforting the grieving, dealing with rape survivors, healing from generational trauma, and navigating violent or emotionally charged environments. Review questions and practical tools are included to enhance training, teaching and certification programs. Whether you're a chaplain, pastor, caregiver, or Christian counselor, The chaplain's calling will empower you to carry the light of Christ into the darkest moments of human experience-- with honor, skill and heart. "- back cover
Keywords: Chaplaincy service; Chaplains